Indigenous peoples and the environment: a relationship between prejudices and national interest: Indigenous peoples and the environment: a relationship between prejudices and national interest - Antunes Vieira, Fábio; Mendes, Leandro de Aquino; Almeida, Leila de Souza (Revista Desenvolvimento Social, 2023)
In recent years, especially during the Bolsonaro government, Brazil has moved in the opposite direction to the appreciation of its natural capital. In relation to the Amazon forest, for example, deforestation threatens its existence as a tropical forest and has caused an imbalance in rainfall regulation, in addition to environmental damage at a global level. Faced with such a fatalistic perspective, it is up to public authorities and organized civil society to seek alternatives that guarantee the sustainable enjoyment of the national natural capital, in order to enable the continuity of life in its multiple dimensions. To this end, no discussion could do without the knowledge of indigenous peoples who, guided by a more harmonious relationship with “mother earth”, demonstrate that it is possible to reconcile environmental preservation with economic exploitation. However, victims of prejudice, violence and greed for their land, they have been excluded from the decision-making process. Considering the context presented, the objective of this article is to include indigenous peoples in the midst of the environmental debate in Brazil, especially with regard to the green economy, in order to highlight that, contrary to common sense, the so-called “white men” need more of them, than the opposite.